2015
DOI: 10.1177/1056789515582277
|View full text |Cite
|
Sign up to set email alerts
|

A damage model for ductile porous materials with a spherically anisotropic matrix

Abstract: In the present study, we investigate the macroscopic strength of ductile porous materials having a Hill-type radial anisotropic matrix. The procedure is based on a limit analysis (LA)-based kinematic approach of a rigid plastic hollow sphere. We first established the exact solution (stress and velocity fields) to the problem of the hollow sphere subjected to an external hydrostatic loading. Then, we propose, for general loadings, an appropriate trial velocity field which allows to implement the kinematic LA pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…A new theoretical nonlinear creep damage model Yang et al (2002) suggested that a nonlinear hardening phenomenon existed in the stage of rock decay and steady-state creep, with little or no damage inside the rock, which can be neglected. As rocks are continually loaded to the accelerating creep stage, damages increase and display distinct nonlinear characteristics (Nezhad et al, 2016;Pensee et al, 2016). Therefore, we assumed that rocks would not experience damage until entering the accelerating creep stage.…”
Section: Introductionmentioning
confidence: 99%
“…A new theoretical nonlinear creep damage model Yang et al (2002) suggested that a nonlinear hardening phenomenon existed in the stage of rock decay and steady-state creep, with little or no damage inside the rock, which can be neglected. As rocks are continually loaded to the accelerating creep stage, damages increase and display distinct nonlinear characteristics (Nezhad et al, 2016;Pensee et al, 2016). Therefore, we assumed that rocks would not experience damage until entering the accelerating creep stage.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike brittle and quasi-brittle materials, ductile materials have widespread applications in engineering structures that their static failure is usually gradual and their final fracture takes place in a stable manner [7,8]. Such a failure behavior is mainly due to significant plastic deformations [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…(2011), Kim et al. (2016), Lecarme et al., (2011), Nguyen and Dormieux (2014), Pensée et al. (2015), Rousselier (1987) and Steglich and Brocks (1997).…”
Section: Introductionmentioning
confidence: 99%